Moral message of tolerance in Coki & Muslim's Youtube podcast on Being Human - Jevon Putri Ayunovem Samino; Mochammad Arkansyah (LPPM Stikosa-AWS, 2023)
Moral messages are an important part so that we can add knowledge about the value of life. Moral messages can be conveyed through means of communication, one of which is through mass media that are comprehensive for the community. Submission of information via YouTube can be done quickly, one of which is through Podcasts. This study aims to determine the contents of the moral message contained in the podcast from the perspective of Coki & Muslims about tolerance for diversity and sensitive comedy on YouTube